2011
DOI: 10.1088/0953-2048/24/11/115004
|View full text |Cite
|
Sign up to set email alerts
|

Void and phase evolution during the processing of Bi-2212 superconducting wires monitored by combined fast synchrotron micro-tomography and x-ray diffraction

Abstract: Recent study of the current-limiting mechanisms in Bi-2212 round wires has suggested that agglomeration of the residual Bi-2212 powder porosity into bubbles of filament-diameter size occurs on melting the Bi-2212 filaments.These pores introduce a major obstacle to current flow, which greatly reduces the critical current density (J c ). Here we present an in situ non-destructive tomographic and diffraction study of the changes occurring during the heat treatment of wires and starting powder, as well as a room t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 22 publications
1
46
0
Order By: Relevance
“…Previously we have reported on the formation of porosity and the phase changes occurring in a Bi-2212 wire during processing in pO2=0.21 bar [6]. In this article we report for the first time the direct observation of the phase changes during heat cycles at pO2≥1 bar.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…Previously we have reported on the formation of porosity and the phase changes occurring in a Bi-2212 wire during processing in pO2=0.21 bar [6]. In this article we report for the first time the direct observation of the phase changes during heat cycles at pO2≥1 bar.…”
Section: Introductionmentioning
confidence: 59%
“…During the in situ HTs one pattern was acquired every 5 minutes. More details about the diffraction experiment can be found in [5] and [6].…”
Section: B X-ray Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies by Shen et al [8], Kametani et al [10] and Scheuerlein et al [11] showed clearly that the gas in the wire agglomerates into filament size bubbles when Bi-2212 melts. When Bi-2212 reforms on cooling, the bubbles can be partially filled by new plate-like Bi-2212 grains, but the original bubble structure remains, even in fully-processed wires, leaving unsupported bridges of Bi-2212 shown earlier by Kametani et al [10].…”
Section: Discussionmentioning
confidence: 93%
“…It is well known that long lengths have several times lower J c than short samples and this has meant that so far no Bi-2212 user magnets have been made. The earlier studies of Shen et al [8], Malagoli et al [9], Kametani et al [10], and Scheuerlein et al [11] provide firm evidence that the large gas bubbles formed during the excursion into the melt state provide the major present current-limiting mechanism in round-wire Bi-2212 conductors. A recent study by Malagoli et al [12] on the length-dependent expansion of a Bi-2212 wire after full heat treatment showed that gas pressure provokes a wire diameter expansion which increases with distance from the ends, longer samples (up to 2.4 m) often showing evident damage and leaks caused by the internal pressure.…”
mentioning
confidence: 92%